2005
DOI: 10.1007/s11010-005-7815-1
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of ultrastructural and biochemical changes in alloxan-induced diabetic rat sciatic nerve on treatment with Na3VO4 and Trigonella—a promising antidiabetic agent

Abstract: Vanadium has been reported to have broad pharmacological activity both in vitro and in vivo. Vanadium compound, sodium orthovanadate, Na3VO4, is well known for its hypoglycaemic effects. However, Na3VO4 exerts these effects at relatively high doses (0.6 mg/ml) and exhibit several toxic effects. In the present study lower doses of Na3VO4 (0.2 mg/ml) are combined with Trigonella foenum graecum seed powder (TSP), another hypoglycaemic agent, to reduce its toxicity without compromising its antidiabetic potential. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Hyperglycemia during diabetes has been shown to generate free radicals, increase damage to membranes and decrease antioxidant status (Kumar and Menon, 1993;Preet et al, 2005). Present results showed that three weeks treatment of the diabetic group with insulin, and TSP separately resulted in a marked reduction in hyperglycemia in the diabetic animals (Mohammad et al, 2006;Baquer et al, 2011;Kumar et al, 2011b, c).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Hyperglycemia during diabetes has been shown to generate free radicals, increase damage to membranes and decrease antioxidant status (Kumar and Menon, 1993;Preet et al, 2005). Present results showed that three weeks treatment of the diabetic group with insulin, and TSP separately resulted in a marked reduction in hyperglycemia in the diabetic animals (Mohammad et al, 2006;Baquer et al, 2011;Kumar et al, 2011b, c).…”
Section: Discussionmentioning
confidence: 53%
“…Lipid peroxidation of the neuronal membrane causes loss of membrane fluidity and inhibition of membrane linked enzymes, increased neurolipofuscin deposition leading to diminished neurotransmitter uptake and loss of membrane asymmetry (Kamboj et al, 2009;Baquer et al, 2011). Previous studies from our laboratory have demonstrated that oral administration of Trigonella foenum-graecum seed powder to diabetic animals can lower blood glucose levels and partially restore the activities of key enzymes of carbohydrates and lipid metabolism to near normal levels in various animal models of diabetes (Raju et al, 2001;Preet et al, 2005;Mohammad et al, 2006;Baquer et al, 2011;Kumar et al, 2011b, c).…”
Section: Introductionmentioning
confidence: 99%
“…It plays an important role in detoxification and in the protection of cellular constituents against reactive oxygen species (Preet et al, 2005). Loven et al (1986) suggested that a decrease in hepatic GSH could be the result of decreased synthesis or increased degradation of GSH by oxidative stress in STZ-induced diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in ROS scavenging compounds may be due to the direct affect of diabetes and aging on scavenger production or activity, like enhanced protein glycation may be responsible for the reduced enzymatic anti-oxidant activity of superoxide dismutase Mohamad et al 2004). Alteration of glutathione levels may be related to an increased polyol pathway (Preet et al 2005) activity as this leads to a depletion of NADPH which is necessary for the enzymatic reduction of oxidized glutathione (Fig. 2).…”
Section: Diabetic Neuropathy-peripheral and Central Nervous Systemmentioning
confidence: 99%